How Might the Relation of the Development of Hand Preferences to the Development of Cognitive Functions be Examined During Infancy: A Sketch? - Michel, George F. (Frontiers in Neuroscience, 2018)
Investigations of the relation of the development of hand preferences to the development of other sensorimotor and cognitive abilities are plagued by confusing and contradictory results. In part, the confusion derives from the failure to create accurate, appropriate and reliable descriptions of the development of hand preferences and the cognitive or sensorimotor ability of interest. This paper sketches an ideal longitudinal study (from birth through 5 years) with a large sample size that ought to be able toshould provide reliable evidence for the understanding of the relation of hand preferences to cognitive development. Since hand preference differences would affect the way infants engage in manual actions with objects and these differences would likely affect how they come to comprehend object relations, differences in the development of cognition across handedness groups would be a good test of certain forms of embodiment theory.